Analisis Semiotika Film Sinema Wajah Indonesia Sandal Butut - Jamilah Jamilah (STID DI AL-HIKMAH, 2017)
The purpose of this study did not look for or explain the relationship, do not test the hypothesis or prediction, but to examine the moral meaning in the face of Indonesian Cinema Film Slippers Butut is to analyze the moral and social krtitik in various scenes are displayed. The method of analysis is Semiotics Roland Barthes who use the term to indicate the denotation and connotation levels of meaning. Conclusion of the study, Cinema Film Indonesia Slippers Butut face is a representation of the social conditions of the middle to lower Meaning denotation indicated when residents disturbed by residents who lost slipper. Connotations depicted in the television film is a picture of the simplicity of small communities with diverse complexity of social problems. Myths which emerged characterized by thieves Slippers disease kleptomania. Moral messages contained in the film is the patient, must not accuse someone without definite proof, being ascetic, uphold tolerance, mutual respect and helping in social life.